Gambaran Klasifikasi Pasien Di Ruang Rawat Inap Rumah Sakit Orthopedi Prof. Dr. R. Soeharso Surakarta - Pinasti, Safira Rizky; , Arum Pratiwi, S.Kp., M.Kes (2016)
Patient classification is a method of classifying patients according to the number of kompleksifitas needs of nursing, with patient classification can determine much and what kind of personnel required and determine the value of productivity so that the number of nurses with patient needs can be balanced. This study aims to describe the classification of patients hospitalized in the Orthopaedic Hospital Prof. Dr. R. Soeharso Surakarta. This study is a descriptive analysis with cross sectional approach. The study population was all inpatients diruang grade 1, 2 and 3 RSO Prof. Dr. R. Soeharso Surakarta and a sample of 75 patients with accidental sampling technique. Collecting data using observation sheet classification of medical surgery, while data analysis using quantitative descriptive by using test Central Tendency. The conclusion of the study the personal characteristics of the client's hospitalization in RSO Prof. Dr. R. Soeharso Surakarta mostly aged 21-45 years, male gender, work as self-employed, earn 1-2 million, most experienced Post ORIF calceneus and post citodebridement, and length of stay is less than or up to 1 week, description the characteristic length of stay clients with surgical medical classification levels showed no particular inclination in view of the length of hospitalization of patients in RSO Prof. Dr. Soeharso Surakarta, and the category of medical-surgical clients in inpatient RSO Dr. R. Soeharso Surakarta mostly intermediate care.